Uses of Learning Media for Improving the Use of Proverbs in Communication of Students with Vision Disabilities - Ariyanuwat Samathayakul; Suchalak Thamaduangsri (Journal of Educational Issues, 2024)
The purposes of the study were (1) to develop a learning media for improving the use of proverbs in the communication of students with vision disabilities, (2) to study the effect of the developed media on the use of proverbs in the communication of students with vision disabilities, and (3) to study students’ satisfaction toward the developed media. The study was divided into two phases the development of learning media and the implementation of the media. The participants were a group of 5 scholars in related areas employed in developing the learning media and a group of 7 visually impaired students employed in the implementation phase. The instruments were a learning media developed in an audiobook in the DAISY system, a media evaluation form, a pre-posttest, and a questionnaire. The data were analyzed using the mean score, standard deviation, t-test, and content analysis. The results of the study show that (1) the learning media for improving the use of proverbs in the communication of students with vision disabilities was designed in an audiobook in the DAISY system and evaluated to be appropriate by experts in the area; (2) The developed learning media was effective in developing the use of proverbs in the communication of students with vision disabilities; (3) the developed learning media could bring about satisfaction in learning to a language class of visually impaired learners. The results of the study could be beneficial for teachers seeking ideas in managing language classes with blind students and scholars who are interested in studying how assistive technology help visually impaired students learn language skills.